Kajian Manfaat Dan Willingness to Pay Masyarakat Terhadap Layanan Instalasi Pengolahan Lumpur Tinja (IPLT) Di Kota Bintuhan - Marfi, Sasdar; Barchia, M. Faiz; Yurike, Yurike; Brata, Bieng; Santoso, Urip (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
The construction of a Faecal Waste Treatment Plant (IPLT) in Tanjung Besar Village, South Kaur District, Bintuhan City, Kaur Regency in 2020 is one of the sanitation programs to help reduce the impact of pollution caused by fecal waste in the community environment with an integrated fecal waste processing system before being discharged into surface water. . According to data from the Public Works Sector Division of the PUPR Service as the manager of the Bintuhan City IPLT, this IPLT is not yet running, is still in the trial stage and will only be formed and a Management Decree (SK) will be proposed and is still in the stage of studying strategies and management in its management. Therefore, an analysis is needed to determine the ability to pay community fees as users of IPLT services. This research conducts a study of people's purchasing power which includes analysis of the ability to pay (abbreviated as ATP) and analysis of the willingness to pay (willingness to pay) abbreviated to WTP for the tariffs applied. In this research, questionnaires were distributed using a simple random sampling method and then the results were analyzed using the SPSS (Statistical Package for Social Sciences) and Microsoft Office Excel programs. Then the tariff calculation uses the ATP and WTP methods. The results of research on the community show that people who use fecal waste treatment installation services respond quite well in relation to waste water management. Proportional ATP Value Rp. 25,197.10,- greater than the Proportional WTP value of Rp. 10,064.76,- so it can be seen that the ability of IPLT service users to pay is greater than their willingness to pay. The results of the ATP and WTP calculations show that the applicable tariffs are in accordance with the ability and willingness of the IPLT user community in Bintuhan City.   Keywords: Capacity, Rawas River, Water Class